"Very busy": daily reorganization of mothers to care of children with Congenital Zika Syndrome - Paulo Roberto Lima Falcão do Vale; Deisyane Vitória Alves; Evanilda Souza de Santana Carvalho
ABSTRACT Objective: To understand the experiences and care practices of mothers of children with congenital Zika syndrome. Methods: A qualitative study with collection held in Feira de Santana - Bahia, between September and November 2017, from in-depth interviews and Story-Drawing with 11 family members of children, using thematic content analysis. Results: Mothers take care from experiences with health professionals and groups of mothers. They reorganize themselves in order to optimize time, streamline domestic activities, teach family members, and navigate care spaces. They experience the routine organizing the home, taking care of the children and, specifically, the child with syndrome, referring to: bedtime; giving a shower; changing diapers; feeding; playing; and, stimulating, actions mediated by intense crying and environmental preparation. Conclusion: The experiences are unique and exceptional, conforming the social representation of the mothers as a group, the "mothers of micro", an aspect that differs from other experiences.